2009
DOI: 10.1159/000232449
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin3F Down-Regulates the Expression of Integrin α<sub>v</sub>β<sub>3</sub> and Sensitizes Multicellular Tumor Spheroids to Chemotherapy via the Neuropilin-2 Receptor in vitro

Abstract: Background: Multicellular resistance (MCR), i.e. decreased sensitivity to anticancer drugs compared with common monolayer cell (MC) cultures, depends partly on tumor cell-cell adhesion. Previous studies have shown that anti-adhesive therapies, including integrin αv, β1 and αvβ3 targeting, induced apoptosis and reversed the sensitivity of MCR. Methods: A model of three-dimensional cell culture was used to establish HT29 multicellular spheroid cells (MCS) and explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 55 publications
(43 reference statements)
0
22
0
Order By: Relevance
“…Since U251MG cells have NRP2, the receptor for SEMA 3G and SEMA 3F, and SEMA3F blocked tumor formation by associating with loss of activated αvβ3 integrin, impaired cell adhesion to extracellular matrix components (36,41,42), it could be informative to determine the mechanism of SEMA3G in tumorigenesis and invasive progression.…”
Section: Discussionmentioning
confidence: 99%
“…Since U251MG cells have NRP2, the receptor for SEMA 3G and SEMA 3F, and SEMA3F blocked tumor formation by associating with loss of activated αvβ3 integrin, impaired cell adhesion to extracellular matrix components (36,41,42), it could be informative to determine the mechanism of SEMA3G in tumorigenesis and invasive progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that the most common tumor suppressor gene of endometrioid carcinoma, PTEN, is involved in the interaction of PINCH-ILK by the Pi3 kinase pathway [26] . Thus, the role of PINCH as a crucial adapter protein between integrin and growth factor signal transduction pathways, like other molecular targeted agents, merits further study in the treatment of endometrial cancer and other common malignant tumors after surgical resection, hormonal therapy, radiation and chemotherapy [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Several class 3 SEMAs, including SEMA3A, SEMA3B, SEMA3E and SEMA3F, have been characterized as anti-angiogenic agents (14)(15)(16)(17)(18)(19). For example, SEMA3B, SEMA3F and SEMA4D regulate tumor angiogenesis, growth and metastasis in different manners (20,21). Previous studies showed that SEMA3A, which is considered as the candidate tumor suppressor, is often downregulated in numerous types of cancer, including…”
Section: Introductionmentioning
confidence: 99%